The environmental impact of mycoprotein-based meat alternatives compared to plant-based meat alternatives: A systematic review - Maria Shahid; Pankti Shah; Khanh Mach; Bibi Rodgers-Hunt; Tim Finnigan; Gary Frost; Bruce Neal; Michalis Hadjikakou (Future Foods)
Meat-based foods have significant environmental impacts that are lower for plant-based meat alternatives. Fungi-based mycoprotein offers another alternative to meat, but its comparative environmental impacts have not been comprehensively reviewed. We identified life cycle assessments (LCAs) of mycoprotein-based meat alternatives using ProQuest, Scopus and Web of Science, and the grey literature. Studies were included if they were published in the English language from 1 January 2013 until 18 September 2023, reported process-based LCAs with functional units by product weight, and reported any environmental impact measure, system boundary, or region. Data for mycoprotein was compared against plant-based meat alternatives for base-protein, burgers, mince and sausages, and against meats. Five LCAs of mycoprotein-based products were identified. Greenhouse gas emissions (GHGe) were lower for mycoprotein (0.73 kgCO2eq/kg) compared to soy (1.21 kgCO2eq/kg) or pea protein concentrate (1.91 kgCO2eq/kg). GHGe for mycoprotein-based product types were lower than or comparable to equivalent plant-based products, and lower compared to meat. GHGe from the ingredient production stage were generally lower for mycoprotein-based products compared to plant-based products. Further data are needed to compare land use and water scarcity impacts. Mycoprotein offers clear environmental advantages over meat, but distinctions between mycoprotein and plant-based alternatives require more comprehensive data.